2017
DOI: 10.5312/wjo.v8.i12.895
|View full text |Cite
|
Sign up to set email alerts
|

Season of the year influences infection rates following total hip arthroplasty

Abstract: AIMTo research the influence of season of the year on periprosthetic joint infections.METHODSWe conducted a retrospective review of the entire Medicare files from 2005 to 2014. Seasons were classified as spring, summer, fall or winter. Regional variations were accounted for by dividing patients into four geographic regions as per the United States Census Bureau (Northeast, Midwest, West and South). Acute postoperative infection and deep periprosthetic infections within 90 d after surgery were tracked.RESULTSIn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 36 publications
0
33
3
Order By: Relevance
“…Staphylococcus aureus is the most common pathogen isolated from chronic osteomyelitis [4], with 50% of prosthetic joint infections caused by hardto-treat methicillin resistant S. aureus (MRSA) [2,5]. Despite advances in medical technology, the incidence of infection across all classes of orthopaedic subspecialties ranges from 0.1-30% [4] and rates of reinfection following revision surgery remain as high as 33% [6,7]. Further, the recurrence of S. aureus osteomyelitis following decades of quiescence and presumptive cure remains an important clinical problem [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus aureus is the most common pathogen isolated from chronic osteomyelitis [4], with 50% of prosthetic joint infections caused by hardto-treat methicillin resistant S. aureus (MRSA) [2,5]. Despite advances in medical technology, the incidence of infection across all classes of orthopaedic subspecialties ranges from 0.1-30% [4] and rates of reinfection following revision surgery remain as high as 33% [6,7]. Further, the recurrence of S. aureus osteomyelitis following decades of quiescence and presumptive cure remains an important clinical problem [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…aureus (MRSA) [ 2 , 5 ]. Despite advances in medical technology, the incidence of infection across all classes of orthopaedic subspecialties ranges from 0.1–30% [ 4 ] and rates of reinfection following revision surgery remain as high as 33% [ 6 , 7 ]. Further, the recurrence of S .…”
Section: Introductionmentioning
confidence: 99%
“…Implant‐associated infections are considered very difficult to treat due to the need for complex surgical procedures and prolonged antibiotic therapy 2 . Rigorous intervention studies (i.e., the Surgical Care Improvement Project 3 ) have demonstrated that prosthetic joint infections (PJIs) complicate 0.1%–30% of total joint replacements, 4,5 and rates of recurrent or persistent infection following a two‐stage revision surgery are as high as 33% 6 . Most recently, an international registry of 192 bone infection patients (157 fracture‐related infections, 7 86 PJI, and 49 osteomyelitis) demonstrated a cure rate of only 62.1% at 1 year postoperation.…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal infections (MSKI) remain a devastating complication of orthopedic surgery, the majority of which are caused by Staphylococcus aureus , and in some regions over 50% of cases involve methicillin‐resistant S. aureus (MRSA) strains . Rigorous intervention studies (e.g., outcomes from the Surgical Care Improvement Project) have demonstrated that infection rates for elective surgery cannot be reduced below 1–2%, and failure rates of revision surgery are as high as 33% . In total, the costs for treatment of implant‐associated infection is projected to exceed $1.62 billion in the United States by 2020 …”
Section: The Significance Of Mski In Terms Of Incidence Current and mentioning
confidence: 99%